To simplify the expression \((7^{-3})^7 \cdot 7^{20} / 6^{-2}\), we can follow these steps:
-
Calculate \((7^{-3})^7\): \[ (7^{-3})^7 = 7^{-3 \cdot 7} = 7^{-21} \]
-
Combine the powers of \(7\): Now we have: \[ 7^{-21} \cdot 7^{20} = 7^{-21 + 20} = 7^{-1} \]
-
Combine with \(6^{-2}\): The expression simplifies to: \[ \frac{7^{-1}}{6^{-2}} = 7^{-1} \cdot 6^{2} \]
-
Rewrite in fraction form: \[ 7^{-1} \cdot 6^{2} = \frac{6^{2}}{7^{1}} = \frac{6^2}{7} = \frac{36}{7} \]
Thus, the simplified expression is: \[ \boxed{\frac{36}{7}} \]